Ruminating cultural legitimacy, contemplating internal obedience: proposing a more innovative approach to enforcing international human rights law - Ismail, Shahrul Mizan; Mahmud Saedon, Mahmud Hamdi (2013)

(untitled)
The apparent inability of the human rights system to function effectively is in many ways closely related to the conceptual framework upon which it was built to operate. The international model which forms the foundation from which human rights law is expected to operate is highly statist in nature, and focuses on the sovereign states as the key law enforcement agencies. It heavily relies upon the premise that governments will faithfully implement international human rights standards within their own domestic systems. In fact, based on the doctrine of “consent” and principles of “state sovereignty” and “non-intervention”, states are deemed independent and free agents. Accordingly they could only be bound by law in the form of “contractual obligations” based on their own consent, i.e. states could only be obliged to comply with international legal rules if they had first agreed to be so obliged through acts of ratifying an international human rights treaty or convention. This leads to the conclusion that the best possible way of fostering compliance among states with human rights law, is to instill internal obedience in states as opposed to stimulating compliance via external dynamics. Using qualitative method of analysis, this paper shall extrapolate the reasons behind state’s compliance (or non-compliance) with international law in general, and analyze whether the same reasons could also be deployed to motivate states to comply international human rights law. In doing so, it shall comparatively examine both the rationalist and the constructivist theories of states’ compliance and subsequently emphasize on the applicability of any or both of the theories in the implementation and enforcement of international human rights law. Hypothesizing that the constructivist theory is more fitting, the paper proceeds to cogitate the relevance of cultural legitimacy as a crucial factor that may bolster internal obedience in states to comply with human rights law. In its final supposition, the paper invites proponents of human rights and the like to explore multiculturalism as a possible innovative approach that could improve the effectiveness of international human rights law enforcement.